Heart chamber [an inquiry about love] - Czernowin, Chaya 1957- (Naxos Rights (Europe) Ltd., 2021)
The works of award-winning composer Chaya Czernowin have been performed worldwide at significant new music festivals and prestigious venues, and she is the first woman to be appointed composition professor at Harvard University. Commissioned by Deutsche Oper Berlin and widely acclaimed in the critical press, "Heart Chamber" uses voice and stage as internalized sonic and visual landscapes to create a genuine multi-sensory musical experience. With only two characters and a hint of a narrative, this is a grand opera on the smallest of transformations, focusing on the intense beauty and vulnerabilities of falling in love. "It is seldom that audiences at the Deutsche Oper Berlin have listened with such rapture to a new commission" (Online Merker)
"A work commissioned by the Deutsche Oper Berlin" - Behältnis
Filmaufnahmen: 13., 26. und 30. November 2019, Deutsche Oper Berlin
Bildformat: Breitbild (1,78:1)
Includes a conversation with the composer by Dorothea Hartmann and notes on the feature film in German with English translation (23 pages : portraits) inserted in container
Keywords: Operas; Documentary films; Feature films; Filmed performances; Film; DVD-Video